STUDI DAYA CERNA ZAT GIZI DAN AKTIVITAS ANTIOKSIDAN TEPUNG KECAMBAH KACANG HIJAU (Phaseolus radiatus L.) - Rachim, Febrielsa Rachmania; Wisaniyasa, Ni Wayan; Wiadnyani, A.A. Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i01.p01, 2020)
The purpose of this study was to determine the nutrient digestibility and antioxidant activity of mung bean sprout flour. This study was conducted using 12 hours germination and without germination of mung bean, and each treatment was repeated three times. Mung bean flour and mung bean sprouts flour were tested for moisture content, ash content, protein content, fat content, carbohydrate content, protein digestibility, starch digestibility, total phenol, and antioxidant activity. The results showed that germination of mung bean had a very significant effect on moisture content, antioxidant activity (IC50), and total phenol, a significant effect on starch digestibility, and had no significant effect on ash content, protein content, fat content, carbohydrate content, and protein digestibility. The results showed that mung bean sprout flour has a moisture content of 6.74%, ash content 3.39%, protein content 32.13%, fat content 11.33%, carbohydrate content 46.41%, protein digestibility 46.80%, starch digestibility 93.45%, total phenol 22.02 mg/100 g, and antioxidant activity (IC50) 454.50 ppm. Keywords : mung bean, sprout flour, nutrient digestibility, antioxidant activity